2017
DOI: 10.1371/journal.pone.0169111
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Soluble C5b-9 Complex in Dialysis Fluid May Predict Poor Prognosis in Peritonitis in Peritoneal Dialysis Patients

Abstract: BackgroundWe searched for indicators to predict the prognosis of infectious peritonitis by measuring levels of complement proteins and activation products in peritoneal dialysis (PD) fluid (PDF) of patients at early stages of peritonitis. We retrospectively analyzed the relationship between the levels of sC5b-9, C3 and C4 in PDF and the subsequent clinical prognosis.MethodsWe measured levels of sC5b-9, C3 and C4 in PDF on days 1, 2 and 5 post-onset of peritonitis in 104 episodes of infectious peritonitis in PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Published studies suggest a promising role for novel biomarkers as risk predictors of adverse outcomes in patients with peritonitis 25 27 . Research in this field may yield information that can be incorporated into our predictive model to establish the prognostic value of these markers, primarily at the early presentation stage of PD-related peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies suggest a promising role for novel biomarkers as risk predictors of adverse outcomes in patients with peritonitis 25 27 . Research in this field may yield information that can be incorporated into our predictive model to establish the prognostic value of these markers, primarily at the early presentation stage of PD-related peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Complement activation products have also been suggested as a biomarker during peritonitis. Mizuno et al showed that C4, C3, and sC5b-9 levels in the peritoneal fluid are significantly higher in PD patients with poor prognosis after peritonitis ( 105 ). Complement markers in peritoneal fluid have, therefore, the potential to serve as a biomarker for the prediction of the prognosis of PD-related peritonitis.…”
Section: Peritoneal Dialysismentioning
confidence: 99%
“…Signs of complement and coagulation cascades activation were noted after exposure to PD fluids or in case of peritonitis, both in rat models but were also reduced after either complement or coagulation inhibition by anti-C5a molecule or low molecular weight heparin (LMWH), respectively, and inversely after enhanced complement activation. 19,51,52 However, few data on the coagulation system’s implication in PD are available and the relevance of coagulation and complement systems interconnection on various PD aspects still remains unknown. Still, human peritoneal mesothelial cells can produce several coagulation factors; among them, plasminogen activator inhibitor 1 could play a role in peritoneal membrane damage such as fibrosis and angiogenesis as well as peritonitis and EPS.…”
Section: The Implications Of the Complement System Activation In Pdmentioning
confidence: 99%
“…38,39,50 In a retrospective analysis, high levels of complement proteins, particularly C5b-9, in PD effluent of patients suffering from early stages of peritonitis were also associated with poor prognosis, defined as withdrawal from PD. 19 Although, it is still unclear whether increased complement activation is itself responsible for the poorer outcomes or if it is the signature of a more severe infection associated with a worse prognosis. On the other hand, it has also been proposed that reduced complement components levels due to intraperitoneal activation could impair host defense and thus increase the risk of peritonitis.…”
Section: The Implications Of the Complement System Activation In Pdmentioning
confidence: 99%